Women in Britain’s Pakistani diaspora and their relationship with formal and informal Labour, 1962-2002 - Din, A (2021)
This thesis is a comparative study of British-Pakistani women’s relationship with formal and informal labour in Middlesbrough and Oldham. The period begins in 1962, when the Commonwealth Immigration Act was enacted, and ends in 2002, when the Nationality, Immigration and Asylum Act was implemented and the ‘Life in the United Kingdom’ test was proposed.